Mediating Effect of Consumer Attitude Variables on the Influence of Store Atmosphere, Brand Awareness, and Product Variety on Purchase Intentions - Taufik, Muhamad; Asih, Daru (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose –This research aims to determine and explain the influence of store atmosphere, brand awareness, product variety on purchase intentions with consumer attitudes as a mediating variable. Methodology/approach –This research is a quantitative research with Lawson shop consumers as the population. The sampling technique was purposive sampling with 150 consumers of the Lawson South Meruya branch as samples. Research hypothesis testing was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.2.9 software Findings – ItThe research results show that independently, the variables of store atmosphere, brand awareness, and product variety have a positive influence on consumers' purchasing intentions at the South Meruya branch of the Lawson store. The consumer attitude variable also has a positive and significant influence on purchasing intentions. The three independent variables mediated by consumer attitudes also have a positive and significant influence on purchase intentions.